The CCR5 receptor acts as an alloantigen in CCR5Δ32 homozygous individuals: Identification of chemokineand HIV-1-blocking human antibodies - Ditzel, Henrik J. (The National Academy of Sciences, 1998)
The chemokine receptor CCR5 is the major coreceptor for infection by macrophage-tropic R5 HIV-1. A 32-bp deletion in the gene coding for CCR5 (CCR5Δ32) occurs with a frequency of 10% in the Caucasian population and results in a receptor protein that is truncated and not expressed at the cell surface. CCR5Δ32 homozygous individuals are apparently normal but resistant to infection with R5 HIV-1. In two individuals homozygous for CCR5Δ32, who had been repeatedly exposed to CCR5-expressing blood cells through sexual activity, we have identified antibodies to CCR5 that bound specifically to the surface of CCR5-expressing cell lines. Serum from these individuals, in contrast to serum from CCR5(+/+) individuals, competed with radiolabeled RANTES for binding to the CCR5 receptor and inhibited infection of peripheral blood mononuclear cells with R5, but not X4, primary isolates of HIV-1. The identified human antibodies to CCR5 define an alloantigen that may cause allograft rejection in a mismatch situation even in individuals with no history of blood transfusions or i.v. drug abuse.